Gender Norms and Other Factors Explaining the Gender Gap in Students’ Entrepreneurial Inclination in Spain and Iceland - Fernández Cornejo, José Andrés; Escot Mangas, Lorenzo; Pozo García, Eva María Del; Cáceres Ruíz, Juan Ignacio (Asian Women, 2018)
This work was supported by Fundación de las Cajas de Ahorro (FUNCAS), and the “Instituto de la Mujer” of the Spanish Government. Young women still have a lower entrepreneurial inclination (EI) than young men in both a Latin society (Spain) and in a Nordic society (Iceland). Our data come from a survey conducted among university students who attended the Complutense University of Madrid and the University of Iceland. After constructing a set of variables and indicators that served as explanatory variables, and after conducting a statistical and regression analysis, this study provides evidence about the determinants of this gender gap in EI. The EI of male students was more sensitive to having higher self-confidence than in the case of female students. In turn, the EI of female students was more sensitive to both positive (enrichment) and negative (conflict) perspectives about the work–family interface than in the case of males. Additionally, the EI of students was positively related with entrepreneurial family antecedents, and with the level of parental income; and it was negatively related with their tolerance for risk. Some cross-cultural differences were also found between the Spanish and Icelandic samples. Depto. de Economía Aplicada, Pública y Política Depto. de Economía Financiera y Actuarial y Estadística Fac. de Ciencias Económicas y Empresariales TRUE pub